2010
DOI: 10.3233/wor-2010-1067
|View full text |Cite
|
Sign up to set email alerts
|

Desire, longing and vanity: Emotions behind successful return to work for women on long-term sick leave

Abstract: Objective: The purpose of this study is to identify situations and phenomena that have simplified returning to work for women on long-term sick leave. Participants: Seven women who were exposed to a relatively large number of risk factors that normally are associated with difficulties in returning to work. Methods: In-depth interviews with qualitative content analysis. Results: The analysis indicated four main categories of factors: The Individual, Interactions, Surrounding Resources, and Situations. In each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 0 publications
5
14
0
9
Order By: Relevance
“…The positive effect of feeling respected on self-estimated ability to return to work was particularly manifested among patients with mental disorders. Our results are in line with previous findings that long-term sick-listed patients are sensitive to whether their encounters are respectful or not [9]. …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The positive effect of feeling respected on self-estimated ability to return to work was particularly manifested among patients with mental disorders. Our results are in line with previous findings that long-term sick-listed patients are sensitive to whether their encounters are respectful or not [9]. …”
Section: Discussionsupporting
confidence: 93%
“…From other studies it has been reported that female sick-listed patients have special preferences when it comes to rehabilitation and return to work [9]. On this backdrop it is interesting that we did not find any gender differences.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…A previous study investigating key factors for RTW in women with chronic pain found that their self-image, strength and desire to work were important. The study also supported the presence of a work ethic in the rehabilitation process [34]. However, they view work ethic as an individual factor, whereas we view it as a societal norm that sometimes causes individuals to stray from their personal goals.…”
Section: Transformative Narrativessupporting
confidence: 73%